The song of lunch [videorecording (DVD)] : a poem - MacCormick, Niall; Rickman, Alan; Thompson, Emma; Reid, Christopher, 1949- (British Broadcasting Corp. : 2 entertain ; Distributed by Warner Home Video, 2012)
The Song of Lunch is based on Christopher Reid's narrative poem following the story of an unnamed book editor who is meeting his former love 15 years after their break-up for a nostalgic lunch at the Soho restaurant they used to frequent. The woman is now living a glamorous life in Paris, married to a world-renowned writer. The unnamed editor has failed in his writing career, detests his mundane publishing job and regrets the end of their love affair.